Efeito da ocitocina comparado ao promestrieno na síndrome geniturinária: estudo piloto randomizadoe e duplo-cego - Santos, Liani Patricia Andrade [UNIFESP] (2021)
Prospective, double-blind and randomized pilot study to compare the effectiveness of oxytocin (OT) in relation to promestriene in improving sexual function, symptoms of vaginal atrophy as well as the clinical and histopathological examination of the vaginal wall in Genitourinary Syndrome of Menopause (GSM). 51 postmenopausal women presenting symptoms of GSM who met the inclusion and exclusion criteria were evaluated. They were randomized into two groups: group 1 (OT) with 25 patients and group 2 (promestriene) with 26. Patients received vaginal OT or promestriene gel and the FSFI domains (lubrication, satisfaction, and pain in sexual intercourse), visual clinical examination and vaginal wall thickness were evaluated before and after 90 days of treatment. Both groups, after the use of the medications showed significant improvement of the three FSFI domains evaluated (p<0.05). And when compared, no differences were revealed (p>0.05). However without statistical significance (p>0.05), the medications presented improvement in all parameters evaluated in the clinical examination. In the evaluation of the thickness of the vaginal epithelium, both treatments, when evaluated separately, presented an increase of the vaginal epithelium after their use however promestriene revealed better effectiveness than OT (p<0.05). Conclusion: After 90 days of vaginal application of oxytocin and promestriene, both were conformably effective in improving lubrication, satisfaction and pain domains obtained from the FSFI score, with no significant variance between them; Even without statistical significance, alterations in the vaginal mucosa visualized on clinical examination were improved; they were effective in increasing the thickness of the vaginal epithelium, with the promestriene showing superior performance. Yet, studies with a longer sample and prolonged time are still necessary to confirm clinical applicability.